Establishment and use of new MDCK II cells overexpressing both UGT1A1 and MRP2 to characterize flavonoid metabolism via the glucuronidation pathway. Issue 9 (6th July 2016) - Wang, Meifang; Yang, Guangyi; He, Yu; Xu, Beibei; Zeng, Min; Ge, Shufan; Yin, Taijun; Gao, Song; Hu, Ming
Abstract : MDCKII‐MRP2‐UGT1A1 cells, which overexpress both UGT1A1 and MRP2, are used to determine how higher expression of efflux transporter will impact the cellular pharmacokinetic of glucuronide formation. The results show that overexpression of MRP2 will significantly increase the cellular excretion of glucuronides and make the cell membrane inconsequential at higher flavonoid concentration, when formation of the glucuronide becomes the rate‐limiting step. Abstract : Scope: The purpose of this study is to characterize how overexpression of an efflux transporter and an UDP‐glucuronosyltransferase (UGT) affects the cellular kinetics of glucuronidation processes. Methods and results: A new MDCK II cell line overexpressing both MRP2 and UGT1A1 (MDCKII‐UGT1A1/MRP2 cells) was developed and used to determine how overexpression of an efflux transporter affects the kinetics of cellular flavonoid glucuronide production. The results showed that most model flavonoids (from a total of 13) were mainly metabolized into glucuronides in the MDCKII‐UGT1A1/MRP2 cells and the glucuronides were rapidly excreted. Flavonoids with three or fewer hydroxyl group at 7, 3′ or 6 hydroxyl group were also metabolized into sulfates. Mechanistic studies using 7‐hydroxylflavone showed that its glucuronide was mainly (90%) effluxed by BCRP with a small (10%) but significant contribution from MRP2. Maximal velocity of glucuronide production MDCK‐MRP2/UGT1A1 cells showed a fairly good correlation ( R 2 >0.8) with those derived using UGT1A1 microsomes, but other kinetic parameters (e.g., Km ) did not correlate. Conclusion: Overexpression of a second efficient efflux transporter did not significantly change the fact that BCRP is the dominant transporter for flavonoid glucuronide nor did it diminish the influence of the efflux transporter as the "gate keeper" of glucuronidation process.